Pseudo-Seq: Genome-Wide Detection of Pseudouridine Modifications in RNA - Carlile, Thomas M. (Methods Enzymol, 2015)
RNA molecules contain a variety of chemically diverse, posttranscriptionally modified bases. The most abundant modified base found in cellular RNAs, pseudouridine (Ψ), has recently been mapped to hundreds of sites in mRNAs, many of which are dynamically regulated. Though the pseudouridine landscape has been determined in only a few cell types and growth conditions, the enzymes responsible for mRNA pseudouridylation are universally conserved, suggesting many novel pseudouridylated sites remain to be discovered. Here, we present Pseudo-seq, a technique that allows the identification of sites of pseudouridylation genome-wide with single-nucleotide resolution. In this chapter, we provide a detailed description of Pseudo-seq. We include protocols for RNA isolation from Saccharomyces cerevisiae, Pseudo-seq library preparation, and data analysis, including descriptions of processing and mapping of sequencing reads, computational identification of sites of pseudouridylation, and assignment of sites to specific pseudouridine synthases. The approach presented here is readily adaptable to any cell or tissue type from which high-quality mRNA can be isolated. Identification of novel pseudouridylation sites is an important first step in elucidating the regulation and functions of these modifications.